I WAS HERE: young mothers who have experienced homelessness use Photovoice and participatory qualitative analysis to demonstrate strengths and assets. (March 2015) - Fortin, Rebecca; Jackson, Suzanne F.; Maher, Jessica; Moravac, Catherine
Inspired by Photovoice, a participatory research methodology, I WAS HERE was a photoblogging workshop in Toronto, Canada, for young mothers who, when they joined, were either homeless or had past experience of homelessness. A participatory qualitative analysis process was developed to support workshop participants in collectively conducting qualitative analysis on a selection of their photoblogs exploring how they view their lives. Five mothers engaged in the participatory qualitative analysis process to categorize their photoblogs into themes. Participants selected over 70 of their personal photoblogs, discussed the meaning of their photoblogs, and categorized them into qualitative themes. One of the mothers continued work on the research by contributing to the write-up of the themes for publication. Participants, through the reflective dialogue, developed nine themes from the photoblogs that describe how they experience motherhood. The resulting nine themes were as follows: 'Family', 'Reality Check', 'Sacrifice for Positive Change', 'Support', 'Guidance', 'Growth and Transition', 'Proud of Becoming/Being a Mother', 'Passing on/Teaching Values' and 'Cherished Moments/Reward for Being a Mother'. These themes illustrate the satisfaction that comes from motherhood, strengths and goals for the future, and the desire for support and guidance. The themes developed from this participatory analysis illustrate that young mothers have a positive view of themselves and their ability to be mothers. This constructive view of young mothers provides an alternative to the negative stereotypes commonly attributed to them. This paper also discusses the strengths and challenges of using a participatory analysis approach. As a research methodology, incorporating procedures for participatory qualitative analysis into the Photovoice process provides an effective mechanism to meaningfully engage participants in qualitative analysis. From a health promotion perspective, using the participatory analysis process expanded the Photovoice methodology to facilitate self-reflection and an empowering collective dialogue among a group of women whose strengths and assets are rarely showcased.